Vibration Diagnostics of CNC Machining Center Spindle - Žarnovský, Jozef; Kováč, Ivan; Mikuš, Rastislav; Fries, Jiři; Mošať, Matúš (Manufacturing Technology Journal, 2019)
The principle of vibrodiagnostics lies in the appropriate measuring and analysis of mechanical vibrations of machinery and constructions in industrial and laboratory environment.The aim of this paper is to perform diagnostic measurements on the most essential parts (spindles) of machinery devices Semico VCM 1000. Measurements were carried out by means of portable vibrodiagnostic measuring device Adash A4900 vibrio M. Vibrodiagnostic itself was realized as a walk-monitoring of machinery state according to corresponding technical standard ISO 10816-3:2009, and of limit values, which took place at regular intervals in the selected organization.
Keywords: Vibrations; diagnostics; spindle; device; speed